AN ANALYSIS ON ENGLISH TEACHER’S STRATEGIES IN TEACHING READING COMPREHENSION IN NEW NORMAL ERA - Desi Wulandari; Masrul Masrul (Journal of English Language and Education, 2021)
Analysis of English teacher strategies in teaching reading comprehension in the new normal era. This study aims to see how the strategies used by English teachers in teaching reading comprehension in this new normal era. This research was conducted at SMPN 3 Kuok. As a research subject, this understanding of reading comprehension involved three English teachers. The design and method used in this research is descriptive research. The author uses telephone interviews by giving questions to each English teacher as an instrument in this study. The results of this study indicate that 3 English teachers at SMPN 3 Kuok use strategies to teach reading even though the teaching process is carried out online with the WhatsApp application. In order for students to stay focused while reading, the teacher prohibits other students from sending messages while other friends are recording sound, this is done in order to remain disciplined and keep students focused and the teacher always gives a message by recording sound. And then provide the opportunity for students to make conclusions, for students who are able to do research who are given an A grade. In this study, the researcher concluded that the strategy in teaching reading and reading carried out by the English teacher at SMPN 3 Kuok was good.